Principles of engineering mechanics - Harrison, H. R. (Edward Arnold, 1994)
Integrating statistics and dynamics, this book supports the study of engineering mechanics for the undergraduate. The theory of two- and three-dimensional dynamics of particles and rigid bodies, leading to Euler's equations, is developed. The vibration of one- and two-degree-of-freedom systems and an introduction to automatic control, now including frequency response methods, are covered. This edition has also been extended to develop continuum mechanics, drawing together solid and fluid mechanics to illustrate the distinctions between Eulerian and Lagrangian coordinates.